Intellectual Capital Disclosure Berbasis Website: Studi Komparasi Perguruan Tinggi di Pulau Jawa dan Non-Jawa - Rahayu, Nika Esti; Sudaryono, Eko Arief (Jurnal Akuntansi dan Bisnis, 2022)
The purpose of this study is to examine the comparison of intellectual capital disclosure in Indonesian higher education located in Java and Non-Java which is carried out through the official website on 2021. The research design is descriptive quantitative with a comparative model. The research sample amounted to 85 universities. The data analysis technique used content analysis and independent samples T-test. The results of the study by content analysis showed that intellectual capital disclosure of state higher education in Java is indeed superior to higher education in Non-Java, both in terms of human capital, structural capital, and relational capital. The results by independent samples T-test showed that there is differences in intellectual capital disclosure at state higher education in Java and Non-Java. The implications of this study is expected to contribute ideas for higher education institutions and other institutions that oversee higher education in Indonesia, so the quality of information disclosure related to intellectual capital will increase in the future. Tujuan penelitian ini adalah mengkaji perbandingan intellectual capital disclosure pada perguruan tinggi Indonesia yang berlokasi di Pulau Jawa dan Non Jawa yang dilakukan melalui website resmi pada tahun 2021. Desain penelitian adalah deskriptif kuantitatif dengan model komparasi. Sampel penelitian berjumlah 85 perguruan tinggi. Teknik analisis data menggunakan content analysis dan uji beda independent samples T-test. Hasil penelitian melalui content analysis menyatakan bahwa intellectual capital disclosure perguruan tinggi negeri di Pulau Jawa memang lebih unggul daripada perguruan tinggi di Pulau Non-Jawa, baik dari aspek human capital, structural capital, maupun relational capital. Hasil uji beda menyatakan bahwa terdapat perbedaan intellectual capital disclosure pada perguruan tinggi negeri di Pulau Jawa dan Non-Jawa. Implikasi penelitian ini diharapkan dapat memberikan sumbangan pemikiran bagi institusi perguruan tinggi serta lembaga lain yang menaungi perguruan tinggi di Indonesia, sehingga kualitas pengungkapan informasi terkait intellectual capital lebih meningkat di masa mendatang.